Analysis of the World Championships 2013 Greco-Roman - Tünnemann, H. (FILA Advanced school for coaches - proceedings 2013, 2013)
1. Introduction 2. Analysis of the Greco-Roman World Championships in Budapest under the aspect of the new rules 3. Country - specific aspects of performance in Budapest 4. Qualitative analysis of combat behaviour 4.1 Bout results of all participants 4.2 Combat behaviour of the nations 4.3 Combat behaviour of the winner 5. Technical structure of the Champions 6. Summary 7. Individual world top performances under technical - tactical aspects